PERFORMANCE ANALYSIS OF MICROSTRIP PATCH ANTENNA FOR UWB APPLICATIONS - kumar, Vishal; Subitha (International Journal of Psychosocial Rehabilitation, 2020)
In the modern world, particularlyduring the last two decades, wireless communications have been established widely and quickly.For future development of personal communication devices will aim at providing communication of pictures, speech and data at anytime and anyplace around the globe. This shows the future correspondence terminal reception apparatuses must meet the necessities of multi-band or wideband to adequately cover the conceivable working groups. In any case, the trouble of antenna configuration increases when the quantity of working recurrence groups are more. Hence, to transmit and receive more data, huge transmission capacities are required which is supported by proper design of antennas at very high operating frequencies. So, in this paper we have surveyed a wide range of methods and techniques of antenna configuration for UWB applications.